Early glucose metabolism in children at risk for type 1 diabetes based on islet autoantibodies compared to low-risk control groups - Helminen, Olli; Pokka, Tytti; Aspholm, Susanna; Ilonen, Jorma; Simell, Olli; Knip, Mikael; Veijola, Riitta (Frontiers in Endocrinology, 2022)
Background Anatomic variation or early differences in glucose metabolism have been linked to the development of type 1 diabetes. We aimed to describe early glucose metabolism based on HbA1c, oral glucose tolerance test (OGTT) and random plasma glucose years before the presentation of type 1 diabetes in five risk groups based on autoantibody combinations. For the first time, we were able to include for comparison children with very low risk of progression to type 1 diabetes. Methods The Finnish Diabetes Prediction and Prevention birth cohort study screened newborn infants for HLA susceptibility to type 1 diabetes since 1994. Those carrying a risk genotype were prospectively followed with islet autoantibody testing. Glucose parameters were obtained starting from the time of seroconversion. By August 31, 2014, 1162 children had developed at least one islet autoantibody and were included in the current study. Type 1 diabetes was diagnosed in 335 children (progressors). In the non-progressor groups, 207 developed multiple (≥2) biochemical islet autoantibodies, 229 a single biochemical autoantibody, 370 ICA only and 64 transient autoantibodies. Children were divided into five risk groups. Glucose metabolism was evaluated. Results We observed lower HbA1c values in early follow-up 4.5 to 6.0 years before diagnosis in the progressors when compared to the same time in children with a single biochemical autoantibody or low-risk (ICA only and transient) participants, who did not progress to clinical type 1 diabetes. However, no such differences were observed in OGTTs or random plasma glucose. The variation was minimal in glucose values in the low-risk groups. Conclusion We report the possibility of early alteration in glucose metabolism in future progressors. This could suggest early defects in multiple glucose-regulating hormones.